Soil characteristics analysis using IoT RM - HB, Mallikarjunaiah; Kumar, Prasanna (International Journal of Computer Sciences and Engineering, 2025)
With the advance in IOT and Sensors have influenced Agriculture in better environment monitoring and rise in yields. Farmers need to know the field environment conditions before sowing during anyseason. Mixed farming and Crop rotation are practiced widely. In different part of the season the soil fertility characteristics would vary. Farmers facing several challenges related to knowing the nutrients of soil. In this work experiment existing models are reviewed and proposed a modelto demonstrate how soil characteristics can be instantly measured to accurate using sensors and monitored in real time. We have used IOT solutions using affordable sensors that reports Air temperature, Soiltemperature, Soil moisture and Water sensors. The collected data is automatically uploaded to cloud using Wi-Fi connectivity. Data analytics is carried out in cloud server and the report can be viewed in real time using Mobile application.